Mechanical behavior of Class i cavities restored by different material combinations under loading and polymerization shrinkage stress. A 3D-FEA study - Ausiello, Pietro; Claramella, Stefano; Lanzotti, Antonio; Ventre, Maurizio; Borges, Alexandre L.S. [UNESP]; Tribst, Joao P. [UNESP]; Dal Piva, Amanda [UNESP]; Garcia-Godoy, Franklin (My University, 2019)
Purpose: To examine the influence of different bulk and block composite and flowable and glass-ionomer material combinations in a multi-layer technique and in a unique technique, in deep Class I dental restorations. Methods: 3D CAD of the sound tooth were built-up from a CT scan dataset using reverse engineering techniques. Four restored tooth models with Class I cavity were virtually created from a CAD model of a sound tooth. 3D-finite element (FE) models were created and analyzed starting from CAD models. Model A with flowable resin composite restoring the lower layer and bulk-fill resin composite restoring the upper layer, model B with glass-ionomer cement (GIC) restoring the lower layer and bulk-fill resin composite restoring the upper layer, model C with block composite as the only restoring material and model D with bulk-fill resin composite as the only restoring material. Polymerization shrinkage was simulated with the thermal expansion approach. Physiologic masticatory loads were applied in combination with shrinkage effect. Nodal displacements on the lower surfaces of FE models were constrained in all directions. Static linear analyses were carried out. The maximum normal stress criterion was used to assess the influence of each factor. Results: Considering direct restoring techniques, models A, B and D exhibited a high stress gradient at the tooth/restorative material interface. Models A and D showed a similar stress trend along the cavity wall where a similar stress trend was recorded in the dentin and enamel. Model B showed a similar stress trend along enamel/restoration interface but a very low stress gradient along the dentin/restoration interface. Model C with a restoring block composite material showed a better response, with the lowest stress gradient at the dentin, filling block composite and enamel sides.